Analisis Redaman Kabel Fiber Optic Patchcord Single Core - Juwari Juwari; Puguh Jayadi; Kelik Sussolaikah (STMIK Budi Darma, 2022)
Fiber Optic attenuation value affects the quality of data transmission. The fiber optic attenuation value can be greater or lower than the standard value. The attenuation value can affect the amount of data transmission sent and received. The attenuation value of single core fiber optic is influenced by various things, one of which is the treatment of the cable itself. Treating the cable by bending and coiling can also affect the damping value. To avoid the high attenuation value of fiber Optic when rolled by doing the rolling process carefully and not twisting during the installation process. The commendation scenario uses Fiber Optic Patchcord, the cable length is 5 meters. From the results of the scenario test on the 3 cables used, the highest attenuation value is in cable C with an attenuation value of 5.39 dB. The highest attenuation is in the 15th winding scenario. Meanwhile, from the 3rd test, the lowest attenuation value is found in cable A with an attenuation value of 1.76 dB. The lowest attenuation at the cable position without a given winding scenario. the more rolls the average damping value will increase the value.